Physical Stability Test of Ethanol Extract Ointment Preparation of Ambon Banana Peel (Musa acuminata cavendish subgroup) - Rafelin Putri Herlambang (Strada Journal of Pharmacy, 2019)
Medical plants found in nature, one of which is the banana plant. Bananas have many benefits but have not been widely used by the public. contains tannins, saponins and flavonoids found in banana hump reported to contain vitamin C, vitamin A, protein and fat which work in the process of wound healing. Ointments are the most suitable preparation for the treatment of burns because they function as carriers of medicinal substances for use on the skin, as lubricants and skin protectors so as to prevent contact of the injured skin surface with external stimuli. Ointment is a semi-solid preparation that is easily applied and used as an external medicine. This study aims to look at the physical stability of the formulation of sakep preparation of ethanol extract of ambon banana peel at concentrations of 10%, 15%, 20%. Evaluation of physical properties includes organoleptic tests, homogeneity, pH, spreadability and adhesion. The test results showed that the best formulation was formulation 3, namely the kapok banana peel extract ointment with a concentration of 20% which met the requirements for pH testing, spreadability test and adhesion ability.